Bio-compatible BCTZ-based piezoelectric nanogenerator as energy harvester and waterdrop counter. Issue 9 (15th June 2017) - Kou, Yanfei; Chai, Xuejun; Yu, Ruien; Liu, Yongjiang; Wang, Zhijian
Abstract: In this work, we prepared lead-free 0.5Ba(Zr0.2 Ti0.8 )O3 −0.5(Ba0.7 Ca0.3 )TiO3 nanorods (BCTZ NRs) by using electrospinning method. XRD, FESEM and Raman were used to characterize BCTZ NRs. XRD pattern showed BCTZ NRs to have tetragonal phase structure. BCTZ NRs were used to fabricate a bio-compatible piezoelectric nanogenerator (pNG). In order to enhance the output property of pNG, dielectrophoresis was employed to align the BCTZ NRs in the PDMS matrix. By tapping the pNG, the open-circuit voltage (Voc ) and short-circuit current (Isc ) of ~0.8 V and ~7 nA were obtained, respectively. Furthermore, the pNG can be used as a water-drops counter. The good electric output performance of BCTZ made it suitable for some control systems of electronic devices.